Learning Motivation Phenomenon among the Elementary Students - Edu, Ambros Leonangung; Jaya, Petrus Redy P.; Ni, Laurentius (International Journal of Elementary Education, 2021)
Motivation is an important factor in dealing with dynamic social demands. This study aims to examine the learning motivation of elementary school students. This research uses survey exploratory research. Researchers conducted a survey of 51 elementary school students. Researchers used a questionnaire as a data collection instrument. The questionnaire was compiled based on four components of learning motivation, namely (1) encouragement for achievement, (2) discipline in learning, (3) readiness to overcome difficulties, and (4) curiosity. The questionnaire uses a Likert scale with the categories "always", "often", "sometimes", and "never". The data was Â analyzed using descriptive statistics. The results showed that in general the students had high motivation. However, this high motivation is not in line with concrete actions that show their enthusiasm for learning. This is because the motivation that develops is actually extrinsic motivation. Students learn to get rewarded or to avoid punishment from the teachers. Nevertheless, the students are aware of their obligations as students and believe in their abilities. This can be used as initial capital to encourage students to improve their learning achievement.Â